Wole Soyinka In Ibadan: Genius In Time & Space (2014)
Psychoanalysis is a method of investigating and enquiring into the state of mind of man, particularly where mental ailments are queried. This approach unravels the depths of the patient's state of mind and is the basis upon which psychotherapy is offered as a procedure for treatment. Sigmund Freud's groundbreaking work on psychopathic characters and character types in literature reveals the depths of benefits common to psychology, psychotherapy and literature. This article is a psychological explication of the psychopathic characters of Adiche's creation. It examines the grave consequences that assumptions of mental health creates within the society.